Pilot Study of a Physician-Delivered Education Tool to Increase Patient Knowledge About CKD - Nunes, Julie Wright (2013)
BACKGROUND: Limited research exists on physician-delivered education interventions. We examined the feasibility and impact of an educational tool on facilitating physician-patient kidney disease communication. STUDY DESIGN: Pilot feasibility clinical trial with a historical control to examine effect size on patient knowledge and structured questions to elicit physician and patient feedback. SETTING & PARTICIPANTS: Adults with chronic kidney disease (CKD) stages 1–5, seen in nephrology clinic. INTERVENTION: One page educational worksheet, reviewed by physicians with patients. OUTCOMES: Kidney knowledge between patient groups and provider/patient feedback. MEASUREMENTS: Patient kidney knowledge was measured using a previously validated questionnaire compared between patients receiving the intervention (April–October 2010) and a historical cohort (April–October 2009). Provider input was obtained using structured interviews. Patient input was obtained through survey questions. Patient characteristics were abstracted from the medical record. RESULTS: 556 patients were included, with 401 patients in the historical cohort, and 155 receiving the intervention. Mean age was 57 ± 16 (SD) years, with 53% male, 81% White, and 78% CKD stages 3–5. Compared to the historical cohort, patients receiving the intervention had higher adjusted odds of knowing they had CKD (adjusted OR, 2.20; 95% CI, 1.16–4.17; p=0.01), knowing their kidney function (adjusted OR, 2.25; 95% CI, 1.27–3.97; p=0.005), and knowing their stage of CKD (adjusted OR, 3.22; 95% CI, 1.49–6.92; p=0.003). Physicians found the intervention tool easy and feasible to integrate into practice and 98% of patients who received the intervention recommended it for future use. LIMITATIONS: Study design did not randomize patients for comparison and enrollment was performed in clinics at one center. CONCLUSIONS: In this pilot study, a physician delivered education intervention was feasible to use in practice, and was associated with higher patient kidney disease knowledge. Further examination of physician delivered education interventions for increasing patient disease understanding should be tested through randomized trials.